The family-specific K-loop influences the microtubule on-rate but not the superprocessivity of kinesin-3 motors - Soppina, Virupakshi (The American Society for Cell Biology, 2014)
The kinesin-3 family (KIF) is one of the largest among the kinesin superfamily and an important driver of a variety of cellular transport events. Whereas all kinesins contain the highly conserved kinesin motor domain, different families have evolved unique motor features that enable different mechanical and functional outputs. A defining feature of kinesin-3 motors is the presence of a positively charged insert, the K-loop, in loop 12 of their motor domains. However, the mechanical and functional output of the K-loop with respect to processive motility of dimeric kinesin-3 motors is unknown. We find that, surprisingly, the K-loop plays no role in generating the superprocessive motion of dimeric kinesin-3 motors (KIF1, KIF13, and KIF16). Instead, we find that the K-loop provides kinesin-3 motors with a high microtubule affinity in the motor's ADP-bound state, a state that for other kinesins binds only weakly to the microtubule surface. A high microtubule affinity results in a high landing rate of processive kinesin-3 motors on the microtubule surface. We propose that the family-specific K-loop contributes to efficient kinesin-3 cargo transport by enhancing the initial interaction of dimeric motors with the microtubule track.